Empowerment of Upstream-Downstream Human Resources As an Efforts to Increase Tapioca Industry Results to Minimize Tapioca Import - Banowati, Eva; Sadiyah, Yul Vah; Istiyana, Isma; Arisandi, Hatria Septianingrum (KnE Social Sciences, 2019)
Empowerment of upstream-downstream human resources is a concrete effort made to realize increased production of cassava and tapioca. Where efforts are made is optimization of human resources through information facilitating integrated empowerment of upstream-downstream human resources as social capital and supported by ways to increase cassava and tapioca production in a structured manner so as to make production yields increase. How can the empowerment of upstream-downstream human resources improve the tapioca industry. Adhering to the principles of empowering Human Resources (HR), namely: developing the potential of the community; developing community cooperation; explore community contributions; establish partnerships; and decentralized (independent). The aspects emphasized in this study include access to information, participation, interest / interest, post-harvest processing, and association formation. The application of science and technology to the experimental plot using double row method. the application of science and technology to the pilot plot using cassava cassava seedlings (uj5) in Pati Districts. Keywords: empowerment, import, industry, tapioca, upstream downstream.